Elevating natural science learning achievement: Cooperative learning and learning interest - Mamik Suendarti; Virgana Virgana (Intelektual Pustaka Media Utama, 2022)
Natural science learning achievement is an essential factor in learning outcomes. This research investigated an experimental study that aimed to improve concept science test result in online learning through Jigsaw cooperative learning model and learning style. The research involved the sample of 80 students from junior high school in South Jakarta, Indonesia divided into two groups: the experimental class and the class control. Raw data were statistically analyzed using the two-way variance technique at the .05 significance level. The findings revealed an effect between cooperative learning on natural science learning achievement, learning interest in natural science learning achievement, and interaction between cooperative learning and learning interest in natural science learning achievement. As a result, cooperative learning type Jigsaw shows a significant impact and had a good test result on natural science learning achievement. Therefore, the research suggests that Jigsaw cooperative learning is well suited to use as a learning model among junior high school students based on effect size test results.